Virulence of Meloidogyne spp. and Induced Resistance in Grape Rootstocks - McKenry, Michael V. (The Society of Nematologists, 2007)
Harmony grape rootstock displays resistance to several Meloidogyne spp. but that resistance is not durable in commercial vineyard settings. A 2-year experiment in a microplot setting revealed host specificities of two virulent populations of Meloidogyne arenaria and an avirulent population of Meloidogyne incognita. In a subsequent split-root experiment, the avirulent nematode population was demonstrated to induce resistance to the virulent nematode population. To quantify the level of resistance, reproduction of the virulent nematode population was determined 63 days after being challenged by an avirulent nematode population using a range of inoculum densities and timeframes. Induction of resistance became apparent when the virulent nematode population was inoculated 7 days after the avirulent nematode population and increased thereafter. The level of induced resistance increased with increased inoculum levels of the avirulent nematode population. Root systems of perennial crops are commonly fed upon simultaneously by multiple nematode species. These two studies indicate that field populations can become preferentially virulent upon one or multiple rootstocks and that co-inhabiting populations may induce existing resistance mechanisms. In perennial crops, it is common for numerous nematode species besides Meloidogyne spp. to be present, including some that feed without causing apparent damage.